2004
DOI: 10.1136/bjsm.2003.008193
|View full text |Cite
|
Sign up to set email alerts
|

Little league shoulder syndrome in an adolescent cricket player: Figure 1

Abstract: The first case of little league shoulder syndrome in a cricket player is reported. The condition has been reported in baseball pitchers and is characterised by a proximal humeral epiphyseolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 9 publications
1
27
1
Order By: Relevance
“…Bowling injuries were the most common injuries reported in the present review, 23 24 27 28 29 31 38 39 43 46 47 50 similar to those reported across epidemiological studies. 4 8 10 54 …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Bowling injuries were the most common injuries reported in the present review, 23 24 27 28 29 31 38 39 43 46 47 50 similar to those reported across epidemiological studies. 4 8 10 54 …”
Section: Discussionsupporting
confidence: 80%
“…Thirty-two articles reporting 43 players were found eligible and were included in the current review [ Figure 1 and Table 1 ] 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 with 62% of studies published in the past decade. Seventy-one percent of the case studies were reported from the UK and India [Figures 2 and 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the shoulder, a pitcher may experience a torsional stress to the proximal humeral physis. At the elbow, the young thrower may present with medial epicondylitis, an apophyseal avulsion, as well as an osteochondral defect of the capitellum (6). Both of these represent chronic valgus overload.…”
mentioning
confidence: 99%
“…Other authors have written about this injury, using different names such as proximal humeral epiphyseal osteochondrosis, proximal humeral epiphysiolysis, and stress fracture of the proximal humeral epiphyseal plate (3)(4)(5)(6)(7) . The vast majority of reports address baseball players, but such injury has also been described in cricket players and gymnastic athletes (8,9) . Clinical picture is characterized by shoulder pain of insidious onset progressively worsened during sports practice.…”
Section: Discussionmentioning
confidence: 99%